2023
DOI: 10.29407/nusamba.v8i1.18446
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Ulasan Pelanggan Terhadap Persepsi Resiko Dan Keputusan Pembelian Secara Online

Abstract: Research aim: This study aims to determine the effect of customer reviews on perceived risk, the effect of customer reviews on online purchasing decisions, the effect of perceived risk on online purchasing decisions, and the role of perceived risk in mediating the effect of customer reviews on online purchasing decisions at the Shopee marketplace. Design/Method/Approach: The type of research used is explanatory research, which explores the relationship between research variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…There are several studies that have found research results indicating the influence of trust on purchase decisions, while others have found results showing no influence between trust and purchase decisions. According to Fadhlillah & Hidayati (2022), Mudambi & Schuff (2010) and Isalman et al (2023) there is an influence between trust and purchase intention. However in other studies, Christianie & Sihombing (2021), Arifin et al (2023), andDwidienawati (2020), shows that customer review does not have a significant impact on purchase decisions.…”
Section: Effect Of Customer Review On Purchase Intentionmentioning
confidence: 99%
“…There are several studies that have found research results indicating the influence of trust on purchase decisions, while others have found results showing no influence between trust and purchase decisions. According to Fadhlillah & Hidayati (2022), Mudambi & Schuff (2010) and Isalman et al (2023) there is an influence between trust and purchase intention. However in other studies, Christianie & Sihombing (2021), Arifin et al (2023), andDwidienawati (2020), shows that customer review does not have a significant impact on purchase decisions.…”
Section: Effect Of Customer Review On Purchase Intentionmentioning
confidence: 99%